2012
DOI: 10.1108/00483481211212977
|View full text |Cite
|
Sign up to set email alerts
|

The role of learning agility and career variety in the identification and development of high potential employees

Abstract: PurposeA survey study was conducted in seven best practice organizations in the field of talent management. By cross‐checking their existing high potential lists, the authors aimed to examine to which extent assessments of learning agility were able to predict being identified as a high potential or not above and beyond a baseline prediction by job performance. Furthermore, they aimed to investigate whether learning agility increased with career variety.Design/methodology/approachThe study had a case‐control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 17 publications
2
107
1
2
Order By: Relevance
“…As our data shows, employee assessment is mostly found as a secondary theoretical framework; we found that it most often coincided with an RBV approach (e.g., Dries et al, 2012b), and was also often found in studies that dealt primarily with GTM issues (e.g., Mäkelä et al, 2010;McDonnell, Hickey & Gunnigle, 2011). Dries et al (2012b), in a study examining to which extent assessments of learning agility were able to predict being Studies approaching TM from an employee assessment angle typically aim to identify talent in a valid and reliable manner, advocating the use of standardized tools and methods for evaluating talent (Nijs et al, 2014).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…As our data shows, employee assessment is mostly found as a secondary theoretical framework; we found that it most often coincided with an RBV approach (e.g., Dries et al, 2012b), and was also often found in studies that dealt primarily with GTM issues (e.g., Mäkelä et al, 2010;McDonnell, Hickey & Gunnigle, 2011). Dries et al (2012b), in a study examining to which extent assessments of learning agility were able to predict being Studies approaching TM from an employee assessment angle typically aim to identify talent in a valid and reliable manner, advocating the use of standardized tools and methods for evaluating talent (Nijs et al, 2014).…”
mentioning
confidence: 92%
“…In fact, quantitative research was not found at all prior to 2010, although the number of quantitative studies has accumulated since then and can be expected to increase further in the future, as the use of advanced statistical methods within a field tends to increase as it grows (von Krogh et al, 2012). Logistic regression was a prevalent technique (e.g., Dries, Vantilborgh, & Pepermans, 2012b), as were cluster analysis (e.g., Vivas-López, PerisOrtiz, & Rueda-Armengot, 2011) and structural equation modeling (e.g., Asag-Gau & Dierendonck, 2011). Among the empirical articles, mixed-method studies have been the least frequent (i.e., 11 articles; 7.9%).…”
Section: Preferred Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existem aqueles que estudam a estrutura do callcenter (Bozionelos, 2008), debatem a importância das agências de emprego e relativizam a tradicional condenação a seu tipo de atuação no mercado de trabalho (Smith & Neuwirth, 2009), investigam os principais fatores que afetam a tomada de decisão sobre promoções (Lockamy III & Service, 2011), pesquisam a identificação e o desenvolvimento de pessoas consideradas de elevado potencial para as organizações (Dries, Vantilborgh, & Pepermans, 2012), entre outros (Kellett, Humphrey, & Sleeth, 2009), incluindo a referência ao setor estatal grego (Koskina, 2008) e a crítica foucaultiana à lógica organizacional (Kamoche, Pang, & Wong, 2011).…”
Section: -Gestão Organizacional Da Carreiraunclassified
“…Trata-se de examinar a prontidão de carreira em adolescentes (Usinger & Smith, 2010), delinear uma medida da prosperidade profissional (Porath et al, 2012), avaliar o grau de estresse segundo o gênero (Raghuram et al, 2012), associar traços da personalidade à escolha da especialidade médica em universitários da área (Taber et al, 2011), identificar aspirações profissionais de crianças negras (Watson et al, 2010), mensurar a eficácia de um modelo de desenvolvimento de carreira para adolescentes , comparar a visão sobre certos conceitos de carreira em crianças mais jovens e mais velhas (Howard & Walsh, 2010), determinar fatores de previsão de intenções empreendedoras em adultos (Oschonka et al, 2010) e vários outros (Ashby & Schoon, 2010;Barros & Teixeira, 2011;Blanco, 2011;Brady-Amoon & Fuertes, 2011;Braunstein-Bercovitz et al, 2012;Cha et al, 2009;Cheung & Arnold, 2010;Creed et al, 2010;Decker et al, 2012;Di Fabio & Kenny, 2012;Dipeolu et al, 2012;Domene et al;Dreyfus, 2008;Dries et al, 2012;Duffy et al, 2011;Duffy & Klingaman, 2009;Duffy & Raque-Bogdan, 2010;Emmanuelle, 2009;Faria & Saavedra, 2008;Fernandez-Arata, 2008;Forner & Dulu, 2012;Gibbons & Borders, 2010;Grier-Reed & Skaar, 2010;Grier-Reed et al, 2009;Gunkel et al, 2010;Hirschi, 2010cHirschi, , 2010dHirschi, , 2011a…”
Section: Medição Ou Previsãounclassified